Pemetaan Trase Jaringan Irigasi Melalui Analisis Geospasial (Studi Kasus Daerah Irigasi Cibuluh, Jawa Barat) - Abu Bakar Sambah; Dwi Agus Kuncoro; Syaiful Anam (Jurnal Irigasi, 2017)
Planning of irrigation canal has always faced the problems due to the overlapping of different land use. Irrigation planning should consider the irrigation canals surrounding different land use. Optimization of the determination of the irrigation network must be applied through the assumption of the physical condition of topographical as well as the proximity between irrigation canal and area of irrigation. The aims of this study were: (1) Mapping existing condition of irrigation canals in DI Cibuluh related to the land use and topography of the study area; (2) Mapping and determining the optimal trace irrigation networks based on spatial analysis of the existing land use and topographical characteristics; (3) Establish a simulation concepts of re-classification related to irrigation services area based on the elevation of the study area using geospatial analysis. The study was conducted through geospatial analysis methods in Geographic Information Systems. Digital Elevation Models (DEM) were the basic data in simulating irrigation services area. The results showed that there were two overlapping land use type (forests and industrial areas) that should be subtracted from the irrigated areas. Alignment of Irrigation network was planned without overlapping forest and industrial area, so that the planning was more focus on simulation based on the control points by processing adjustments as well as high elevation contour and water height.